Heaney, Catholicism and the Hauntological: The Later Poetry - Hickey, Ian (ABEI Journal, 2021)
This article looks at Catholicism in Seamus Heaney’s later poetry through the philosophical lens of Jacques Derrida’s work. The theoretical focus of the article is allied to Derrida’s notion of hauntology from Spectres of Marx. During his youth Heaney was a firm believer in Catholicism but as he grew older his faith began to diminish. However, even though he moved to a more secular mode of belief the presence of Catholicism constantly returns to haunt Heaney’s poetry up until his final collection Human Chain. This repetition and return of Catholicism hints at the hauntological as the past sutures itself within Heaney’s thinking and poetic output.